Empowering Tenaga Kependidikan di MA Unggulan Mukhtar Syafa’at Blokagung Banyuwangi - Siti Aimah; Umi Nur Syarifah (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2020)
The applied objectives in this study are: (1) Knowing the recruitment of educational personnel at MA Unggulan Mukhtar Syafa’at Blokagung Tegalsari Banyuwangi Schooling Year 2019/2020; (2) Knowing a placement of educational staff at MA UnggulanMukhtar Syafa’at Blokagung Tegalsari Banyuwangi Schooling Year 2019/2020; (3) Knowing the empowerment of educational staff at MA UnggulanMukhtar Syafa’at Blokagung Tegalsari Banyuwangi Schooling Year 2019/2020; (4) Knowing the supporting and obstacles process of empowering educational staff at MA Unggulan Mukhtar Syafa’at Blokagung Tegalsari Banyuwangi Schooling Year 2019/2020. This research method uses the descriptive qualitative. The data collection through out the observation, interview and documentation. The analysis data uses 3 models of interactive analysis while the technical validity data uses triangulation. The result of the research : the recruitment process of the educational staff at MA unggulan Mukhtar Syafa’at Blokagung Tegalsari Banyuwangi has been running systematically. The placement of adecation personnel at MA unggulan Mukhtar Syafa’at Blokagung Tegalsari Banyuwangi is in accordance with the field of expertise and skills possessed and continued with the guidance which is carried out by the foundation’s management. The process of educational staff empowering has been very good. Supporting and inhibiting factors in the process of empowering educational staff at MA unggulan Mukhtar Syafa’at Blokagung Tegalsari Banyuwangiis: (a) Supporting factors includes the systematic education personnel recruitment (b) Inhibiting factors : (1) there is a limitation of the employees that causes there are currently work educational staff who get unfinished task in accordance with their fields of expertise. (2) There are several types of work that have not been filled.